Analisis Yuridis terhadap Penetapan Batas Minimal Usia dalam Perkawinan Menurut UU No 1 Tahun 1974 tentang Perkawinan Dihubungkan dengan UU No 35 Tahun 2014 tentang Perlindungan Anak - Nuryamin Nuryamin (Al Fuadiy Jurnal Hukum Keluarga Islam, 2024)
The government's goal is to amend the Marriage Law which regulates the minimum age for marriage from 16 years to a minimum of 19 years, has a noble goal because this age is considered mature physically and mentally to be able to enter into a marriage so that it can realize the goals of marriage well without ending in divorce and having children healthy and quality. However, this noble goal is not yet in line with the situation and conditions of the people in certain areas, including cities and regencies in Indonesia, this is reinforced by the increasing number of applications for marriage dispensation that have been submitted to the Religious Courts since the promulgation of Law No. 16 of 2019. Article 23 of Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection explains that the state, government and regional governments guarantee the protection, care and welfare of children by taking into account the rights and obligations of parents, guardians, or other people who are legally responsible for children as well as the state, government and regional governments oversee the implementation of child protection.